Coal cleaning before combustion: Practice and experience in Serbia - Kostović Milena; Simović Ivana; Kostović Nebojša; Pantelić Nina (Podzemni Radovi, 2022)
The paper gives review of international and domestice experience in Serbia in the field of coal cleaning prior to combustion in thermal power plants. Also, the paper highlighted the problem of combustion low rank lignite from open pit mine in thermal power plants and considering this problem from the aspect of mineral processing. The results of laboratory tests aimed to establish the possibility of cleaning of lignite from Tamnava Zapadno polje, showed the beneficial upgrading of the 70% of run-of-mine coal with simple screening. It has been confirmed that by simple process of coal cleaning can be removed about 30% of tailings, which mostly consist of mineral impurities. The final obtained products have satisfactory quality (lower contents of ash and higher calorific values).